2021
DOI: 10.1371/journal.pone.0251475
|View full text |Cite
|
Sign up to set email alerts
|

Attentional shift within and between faces: Evidence from children with and without a diagnosis of autism spectrum disorder

Abstract: Evidence of attentional atypicalities for faces in Autism Spectrum Disorders (ASD) are far from being confirmed. Using eye-tracking technology we compared space-based and object-based attention in children with, and without, a diagnosis of ASD. By capitalizing on Egly’s paradigm, we presented two objects (2 faces and their phase-scrambled equivalent) and cued a location in one of the two objects. Then, a target appeared at the same location as the cue (Valid condition), or at a different location within the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 61 publications
(81 reference statements)
2
4
0
Order By: Relevance
“…Our results (Experiments 1 and 2) replicated the previous findings that faces elicit null or reversed OBA effects (Valenza et al, 2014 ; Xie et al, 2022 ) and further demonstrated that either race or the presence of the eyes was not critical for these results. Experiment 3 introduced a temporal lag between face offset and attentional shifting to avoid any potential attentional filtering cost due to the perceptual or social relevance of faces.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results (Experiments 1 and 2) replicated the previous findings that faces elicit null or reversed OBA effects (Valenza et al, 2014 ; Xie et al, 2022 ) and further demonstrated that either race or the presence of the eyes was not critical for these results. Experiment 3 introduced a temporal lag between face offset and attentional shifting to avoid any potential attentional filtering cost due to the perceptual or social relevance of faces.…”
Section: Discussionsupporting
confidence: 90%
“…However, some studies have found no typical OBA effect in faces, which must be attributed to either shortened RTs in the between condition, the prolonged RTs in the within condition, or both. Valenza et al ( 2014 ) argued that the null OBA effect for faces may be due to the shortened RTs when moving attention between faces (Valenza & Calignano, 2021 ; Valenza et al, 2014 ). They proposed that the display of two faces in the visual field induces a larger attentional focus, leading to faster attentional shifts between faces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that for adult participants, the OBA effect was only found in scrambled faces (i.e., non-face objects), not normal faces (both upright and inverted). The same finding was replicated in typically developing children (Valenza & Calignano, 2021 ). These results indicated that faces tend not to elicit the OBA effect like other objects.…”
Section: Can Faces Elicit Object-based Attention (Oba)?supporting
confidence: 57%
“…This illusory movement perception should employ space-based attention, however, when the instruction was to compare features of the two stationary objects, object-based attention occurred (Zheng and Moore, 2021 ). Surprisingly, this well-established terminology is not in use in developmental psychology, with PsycInfo showing only one study that is using the concept of object-based vs. space-based attention in its abstract (Valenza and Calignano, 2021 ). This is the more astonishing because there is a clear transition in the graphic representations of children from object-based to space-based constructions (Lange-Küttner, 2008a , 2020 ).…”
Section: Introductionmentioning
confidence: 99%